Web 2.0 tools and strategies for archives and local history collections - Theimer, Kate, 1966- (London : Facet, 2010)
'This introductory guide for anyone working with collections in archives and historical organizations will act as a tool to assess the current utility of an organization's web presence, and to identify how to improve that presence using the latest Web 2.0 technologies. Drawing on examples of good practice from real archives websites, providing a wealth of checklists and pinpointing available resources, it offers all that is needed to transform a website to achieve an organization's goals.' --Book Jacket.
'This introductory guide for anyone working with collections in archives and historical organizations will act as a tool to assess the current utility of an organization's web presence, and to identify how to improve that presence using the latest Web 2.0 technologies. Drawing on examples of good practice from real archives websites, providing a wealth of checklists and pinpointing available resources, it offers all that is needed to transform a website to achieve an organization's goals.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Archives -- Computer network resources; Library Web sites -- Design; Web site development; Web 2.0.